Air conditioner consumption optimization in an office building considering user comfort - Mahsa Khorram; Pedro Faria; Omid Abrishambaf; Zita Vale (Energy Reports, 2020)
Rapid growth of energy consumption in last decades, made the world persuaded to energy optimization and management. Therefore, producers and prosumers should be equipped with the automation infrastructures to perform the management programs, like demand response. Office buildings are considering as a proper case for implementing energy consumption minimization since they are responsible for a huge portion of total energy consumption. This paper proposes a multi-period optimization algorithm implemented in Supervisory Control and Data Acquisition system of an office building. The developed optimization algorithm is an efficient solution considered for minimizing the power consumption of air conditioners by considering the user comfort constraints. A case study with several scenarios is implemented to verify the performance of proposed algorithm in real life using real data of the building. The obtained results show the impacts of different comfort constraints of algorithm while the main target of the optimization has been reached.
Keywords: 330; Air conditioner; Multi-period optimization; Office building; SCADA system; User comfort